Preparation and Characterization of Binary and Ternary Complexes of Dihydroartremisinin with Hydroxypropyl-β-cyclodextrin, Palmitic acid and Polyvinylpyrrolidone K30 - Tayyab Ansari, Muhammad; Nadeem, Sumaira; Hussain, Altaf; Majeed, Humaira; Saeed-Ul-Hassan, Syed; Tariq, Imran; Murtaza, Ghulam (Current Pharmaceutical Analysis, 2015)
The objective of current study was to improve solubility of poorly water-soluble antimalarial drug named dihydroartemisinin via the development of binary complexes of DHA with hydroxypropyl-β-cyclodextrin(HP-β-CD), ternary complexes of DHA-(HP-β-CD)-Palmitic acid and DHA-(HP-β-CD)-PVPK30 (PolyvinylpyrrolidoneK30). These complexes were prepared in various drug to excipients ratios by physical mixing and freeze dried (FD) methods. Characterization was performed by powder X-ray diffraction patterns, Scanning Electron Microscopy (SEM), Attenuated Total Reflectance Fourier Transform Infrared Spectroscopy (ATR-FTIR), solubility test, and dissolution studies. Aqueous solubility of binary complexes of DHA increased up to 27 folds, 36 folds in DHA-(HP-β-CD)-palmitic acid and 216 folds in DHA-(HP-β-CD)-PVPK30 ternary complexes. The highest dissolution rate was observed to be 60 times improved for ternary FDCs of DHA-(HP-β-CD)-PVPK30 as compared to pure DHA. The crystallinity of DHA was decreased in physical mixtures while XRD patterns of freeze dried complexes (FDCs) showed least number of peaks having low intensity along with more displaced angles. The SEM images of PMs showed cavities and FDCs exhibited reduced particle size in binary and ternary systems. ATR-FTIR spectra of binary and ternary complexes revealed bonding interactions among DHA, HP-β-CD, palmitic acid and PVPK30. It can be concluded that binary complex formation of DHA with hydroxypropyl-β-cyclodextrin(HP-β-CD) and ternary complexes of DHA-(HP-β-CD)-Palmitic acid and DHA- (HP-β-CD)- polyvinylpyrrolidone K30 is a suitable approach to enhance solubility of DHA.
Keywords: freeze dried binary complexes